Helping Students to Reflect on Their Own Intercultural Learning - Humphreys, Gareth; Hirschel, Rob (International Journal of Multicultural Education, 2025)
This study reports on a qualitative multiple case study evaluating an innovation to enhance student reflection on intercultural learning at a Japanese university. The innovation involved students writing letters to themselves at the start of a 15-week programme and revisiting them at the end. A content analysis using Kember et al.’s (2008) reflective framework compared reflections from 50 students who participated in the innovation with 50 from prior cohorts. The innovation indicated deeper reflection and reassessment of students’ cultural assumptions. By emphasising individual student insights over standardised learning, the study contributes to equity-oriented, context-sensitive approaches to reflection in intercultural learning in higher education.